2010
DOI: 10.1111/j.1365-294x.2010.04892.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and temporal stability of bacterial communities in a model passerine bird, the zebra finch

Abstract: The composition and dynamics of the gastrointestinal bacterial communities in birds is determined by both host-specific and environmental exposure factors yet these are poorly understood. We selected the zebra finch, Taeniopygia guttata, as the host species to examine the diversity and temporal stability of the faecal microflora in a bird, owing to its importance as a model organism in avian ecology, neuroscience and evolution studies. The stability of the gut bacterial community of individual male and female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 97 publications
(207 reference statements)
5
42
0
Order By: Relevance
“…In agreement with our previous observations of low microbial diversity within the kakapo hindgut (Waite et al, 2012, 2013), the diversity estimators for kakapo were among the lowest observed. Consistent with previously reported mammalian findings (Ley et al, 2008a), and with more targeted avian studies (Zhu et al, 2002; Lucas and Heeb, 2005; Banks et al, 2009; Benskin et al, 2010), the host organism was the strongest driver of community structure in the clone-library data and second strongest in the short-read data (Table 3). Other factors were still significantly associated with shaping the gut community but their fit to the data was lower.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with our previous observations of low microbial diversity within the kakapo hindgut (Waite et al, 2012, 2013), the diversity estimators for kakapo were among the lowest observed. Consistent with previously reported mammalian findings (Ley et al, 2008a), and with more targeted avian studies (Zhu et al, 2002; Lucas and Heeb, 2005; Banks et al, 2009; Benskin et al, 2010), the host organism was the strongest driver of community structure in the clone-library data and second strongest in the short-read data (Table 3). Other factors were still significantly associated with shaping the gut community but their fit to the data was lower.…”
Section: Resultssupporting
confidence: 88%
“…Specific studies have addressed areas of avian microbial ecology, such as the variation in microbial diversity along the GI tract (Bjerrum et al, 2006; Gong et al, 2007; Torok et al, 2008; Waite et al, 2012), the influence of diet (Rubio et al, 1998; Blanco et al, 2006; Torok et al, 2008; Janczyk et al, 2009; Hammons et al, 2010), age (Van Der Wielen et al, 2002; Godoy-Vitorino et al, 2010; Van Dongen et al, 2013) or other host-specific factors (Zhu et al, 2002; Lucas and Heeb, 2005; Banks et al, 2009; Benskin et al, 2010; Wienemann et al, 2011). While there is extensive evidence that microbial colonization of the GI tract brings benefits to the host bird (Jin et al, 1998; Torok et al, 2008; Angelakis and Raoult, 2010; Torok et al, 2011; Zhang et al, 2011; Cao et al, 2012; Stanley et al, 2012), there are also pathways through which the normal colonization of microbes can be of detriment to the host (Ford and Coates, 1971; Potti et al, 2002; Cao et al, 2012; Singh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chicken guts are dominated by Firmicutes [62,76], while turkeys' intestinal communities can be dominated either by Firmicutes [37] or Bacteroidetes [62]. In the few wild birds that have been studied, bacterial communities were dominated by Firmicutes; however the second dominant phylum varied: Actinobacteria in Adelaide Penguins and Proteobacteria in Zebra-Finches [6,8]. In the Hoatzin (Ophistocomus hoatzin) a folivorous bird with crop microbial fermentation [20], the microbial community of the crop was dominated by Firmicutes and Bacteroidetes [20,21,22] while the bacterial communities of the foregut were dominated by Bacteroidetes and Actinobacteria, and contained a lower proportion of Firmicutes and Proteobacteria [21].…”
Section: Bacterial Composition Along the House Sparrow's Gutmentioning
confidence: 99%
“…Together these two groups comprise over 96% of all bacterial sequences in the complete gut. The dominance of Firmicutes and Proteobacteria in the intestinal bacterial communities has been reported for other birds like Zebra Finches [8], as well as wild and captive parrots [73]. Because Proteobacteria is a group with a high functional diversity [29], the dominance of Proteobacteria in the House Sparrow gut could be related to its omnivorous diet that includes seeds, insects, fruits, and a large diversity of human food scraps including meat [9,11,49].…”
Section: Bacterial Composition Along the House Sparrow's Gutmentioning
confidence: 99%
“…Birds that defecated during this time were removed for processing, and the feces was transferred to a sterile 2 mL collection tube. Fecal samples are commonly used as proxies for gut microbiotas and allow repeat sampling from the same individual (Benskin et al 2010, De Filippo et al 2010, Degnan et al 2012, Dimitriu et al 2013. Feces was stored in a cooler on ice until the end of the day when it was frozen at À208C until DNA was extracted.…”
Section: Field Samplingmentioning
confidence: 99%